Tracing the Invisible: Lynda Barry’s Comics - Ahmed, Maaheen (Mediascapes journal, 2023)
Turning to Lynda Barry’s distinctive comics which interweave autobiography, fiction, and teaching manuals, this article expands on the different ways in which the invisible is present in Barry’s works, encompassing elements that challenge visual representation and those that constitute the backbone of comics expression. The article unpacks Barry’s incorporation of collage and its constituents of untutored drawing through considering key theories surrounding the trace and the archive. The valorisation of marginalized and ignored image-making practices (such as children’s drawings and untutored drawings) are examined through concepts surrounding animation, possibilities of connecting through drawing and alternative ways of conceptualizing both the making and reception of art.